PAINTING THE WALLS OF AL-IKHLAS MOSQUE IN KAMPUNG WARUNG RT.09 / RW.03, PANYIRAPAN VILLAGE, BAROS DISTRICT, SERANG REGENCY: PENGECATAN DINDING MASJID AL-IKHLAS DI KAMPUNG WARUNG RT.09/RW.03, DESA PANYIRAPAN, KECAMATAN BAROS, KABUPATEN SERANG - Robi Ariansyah; Rayhan Alifa; Cahyo Wibowo (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Painting on walls is the final stage process after sprinkling and plastering on the walls. Painting on the walls functions as beauty in a building. In addition to functioning as an aesthetic beauty, painting on the wall can also be used as wall protection from rain splashes and direct sunlight that can shorten the life of the wall. First prepare the tools and materials used for painting the walls. Supervision is required so that the work or painting is in accordance with the Regulation of the Minister of Public Works on The Maintenance and Maintenance of Building Buildings No. 24/PRT/M/2008. After the painting process is complete, the painting results need to be evaluated/reviewed to ensure that all parts of the wall are painted neatly and cleanly. If a wall is found with uneven paint, it is necessary to repaint the section until the result is neat and even. Furthermore, if you are sure that all the walls are painted neatly and cleanly, then it is only a matter of time before the paint dries. The type and quality of wall paint used is prioritized for domestic production in accordance with the Joint Decree of the Minister of Trade and Cooperatives, Minister of Industry & Menpen. No. 472/Kop/XII/80, No. 813/Menpen/1980, No.  64/Menpen/1980, December 23, 1980. special methods before painting, one of which is the sanding process on the walls from the remaining cement from the results of sprinkling, so that during the painting process a smooth and even wall surface is obtained